2012
DOI: 10.18632/oncotarget.689
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing identifies ATRX mutation as a key molecular determinant in lower-grade glioma

Abstract: The molecular foundations of lower-grade gliomas (LGGs)—astrocytoma, oligodendroglioma, and oligoastrocytoma—remain less well characterized than those of their fully malignant counterpart, glioblastoma. Mutations in isocitrate dehydrogenase 1 and 2 (IDH1/2) likely represent initiating pathogenic events. However, while IDH mutations appear to dramatically alter cellular epigenomic landscapes, definitive downstream transformative mechanisms have not been characterized. It remains likely, therefore, that addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
190
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(205 citation statements)
references
References 38 publications
(63 reference statements)
12
190
2
1
Order By: Relevance
“…Thus, in several clinical studies, mutations in ATRX were found to be tightly associated with the ALT pathway in various types of tumors (10,11,(20)(21)(22)(23). This correlation has also been observed in cultured cells (24,25).…”
Section: Atrx Localizes To Subtelomeric Regions Of Human Glioma Cellsmentioning
confidence: 71%
“…Thus, in several clinical studies, mutations in ATRX were found to be tightly associated with the ALT pathway in various types of tumors (10,11,(20)(21)(22)(23). This correlation has also been observed in cultured cells (24,25).…”
Section: Atrx Localizes To Subtelomeric Regions Of Human Glioma Cellsmentioning
confidence: 71%
“…Recent work has shown that mutations in the SWI/SNF chromatin regulator ATRX frequently occur in gliomas, and are almost invariably associated with mutations of TP53 and IDH1 genes across glioma entities (58,64,65). A strong correlation between inactivation of ATRX and the phenomenon known as alternative lengthening of telomeres has been postulated (64).…”
Section: Atrx Mutations and Tert Alterationsmentioning
confidence: 99%
“…The biological impact of ATRX mutations in humans appears to vary according to the extent and timing of disruption. In humans, ATRX somatic frameshift and nonsense mutations that completely abolish protein function have been identified in pancreatic neuroendocrine tumors (PanNETs) (5-7), pediatric and adult glioblastomas, and other cancers of the CNS (8)(9)(10)(11)(12), underscoring the anti-tumorigenic roles of ATRX. Tumors with ATRX mutations often harbor long telomeres, which are characteristic of the telomere maintenance mechanism known as alternative lengthening of telomeres (ALT) (6,7,11,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, ATRX somatic frameshift and nonsense mutations that completely abolish protein function have been identified in pancreatic neuroendocrine tumors (PanNETs) (5-7), pediatric and adult glioblastomas, and other cancers of the CNS (8)(9)(10)(11)(12), underscoring the anti-tumorigenic roles of ATRX. Tumors with ATRX mutations often harbor long telomeres, which are characteristic of the telomere maintenance mechanism known as alternative lengthening of telomeres (ALT) (6,7,11,13,14). Conversely, hypomorphic inherited mutations of the ATRX gene cause a rare developmental disorder, ATR-X syndrome (OMIM 301040), with diagnostic features of severe cognitive deficits, microcephaly, seizures, short stature, developmental delay, and α-thalassemia, without increased neoplasia incidence (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%